The Faith of the Righteous According to Habakkuk 2:4b and Romans 1:17 - Viktorahadi, R. F. Bhanu (Sekolah Tinggi Theologia Jaffray, 2021)
Habakkuk’s prophecy that the righteous will live by his belief (Hab. 2:4a) resonates in Paul’s letters, especially the text of Roma ns 1:17. This paper describes the authentic meaning of the term ‘believe’ in Habakkuk’s prophecy. Furthermore, this accurate meaning gets a more specific articulation in Paul’s idea of faith. This paper uses the Historical-Critical method and analyzes the text of Habakkuk 2:4b and the text of Rome 1:17. The correlation between these two texts comes to formulate the faith of the righteous in Christianity, namely credibility, justice, firmness, and faithfulness in carrying out the truth based on love, credibility, justice, firmness, and loyalty to fulfil God’s will.